(untitled) (Third Sector Social Economic Review, 2022)
Individuals can take action by being affected by the scenes in the TV series or movies they watch. The desire to experience the same feeling as in the TV series or movie they watch in the destination shown affects the travel plans of individuals. In this context, the food and beverages shown in a series have a great effect on creating/developing a destination image. Because the food and beverages shown in TV series or movies reflect the culture of that destination and the audience adopts this different culture. Over time, potential tourists want to experience this different culture in that destination and organize their travel plans accordingly. Tourists visiting this region bring many benefits, especially economic ones. In summary, gastronomic products shown in a television series contribute to both country and regional tourism in many ways. In this study, which was prepared in this direction, it was aimed to determine the gastronomic products offered to the audience in the television series Gönül Mountain, which was broadcast on TRT 1 and had high ratings since the day it was broadcast. For this purpose, some parts of the series were examined and the gastronomic items in the series are basic products such as tea, Turkish coffee, cheese, olives, jam, rice, these items generally consist of the same products, there is not much variety, and local products are not included, Information on the preparation processes of the products was not provided and the results were obtained. According to the results obtained, some suggestions were made to the relevant people.